PROMOTING AN INDIANISATION MODEL OF RURAL COMMUNITY ENGAGEMENT IN HIGHER EDUCATION INSTITUTIONS OF SOCIAL WORK IN GUJARAT - Mishra, Shivani; Dash, Debendra Nath; Ram, Kera (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The famous saying of Fredrick Muller is always fascinating about India, that goes -“If I were to look over the whole world to find out the country most richly endowed with all the wealth, power, and beauty that nature can bestow – in some parts a very paradise on the earth- I should point to India…and if I were ask to myself from what literature we, here in Europe, who have been nurtured almost exclusively on the thoughts of Greeks and Romans, and of one Semitic race, the Jewish, may draw that corrective which is most wanted in order to make our inner life more perfect, more comprehensive, more universal, in fact more truly human, a life not for this life only, but transfigured and eternal life- again I should point to India.”